Electrical theory AC circuits - Primedia Workplace Learning ([United States] : PRIMEDIA Workplace Learning)
This interactive training unit is designed to familiarize trainees with basic concepts associated with the operation of AC circuits. After completing this unit, trainees should be able to explain how current flows through AC circuits and how AC current and voltage are affected by inductance and capacitance. They should also be able to define true power, reactive power, apparent power, and power factor, and to identify various types of single-phase and three-phase systems.
Keywords: Electrical engineering; Electricity